2021
DOI: 10.1007/s00405-021-06719-3
|View full text |Cite
|
Sign up to set email alerts
|

Management of tympanic membrane retractions: a systematic review

Abstract: Importance Tympanic membrane retraction (TMR) is a relatively common otological finding. However, no consensus on its management exists. We are looking especially for a treatment strategy in the military population who are unable to attend frequent follow-up visits, and who experience relatively more barotrauma at great heights and depths and easily suffer from otitis externa from less hygienic circumstances. Objective To assess and summarize the available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…The biological difference between the pars tensa and pars flaccida can be found in the lamina propria. The lamina propria of the pars flaccida consists primarily of loose and unorganized connective tissue and is thicker than the pars tensa 19 . The unorganized fibers in its connective tissue make the structural arrangements within the pars flaccida weaker and more likely to retract 20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological difference between the pars tensa and pars flaccida can be found in the lamina propria. The lamina propria of the pars flaccida consists primarily of loose and unorganized connective tissue and is thicker than the pars tensa 19 . The unorganized fibers in its connective tissue make the structural arrangements within the pars flaccida weaker and more likely to retract 20…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this analysis shows that the maximum radii between the umbo and the tensa. 19 The unorganized fibers in its connective tissue make the structural arrangements within the pars flaccida weaker and more likely to retract. 20 In agreement with our analysis, Paço et al 10 found that the SPQ has the largest area, representing 28.7% of the area of the eardrum.…”
Section: Discussionmentioning
confidence: 99%
“…1 Chronic otitis media is an inflammatory condition that affects the middle ear and can cause atelectasis, perforation, tympanosclerosis, retraction pocket formation, and cholesteatoma. 2 The tympanic membrane becomes floppy and forms a retraction pocket when there is a fluctuating or prolonged negative middle ear pressure. Adhesive otitis media develops as a result of retraction and related middle ear inflammation.…”
Section: Introductionmentioning
confidence: 99%